Evaluasi Kepatuhan Checksheet dan Coorporate Life Saving Rules Pada Pekerjaan Listrik Di PT. Pertamina Patra Niaga RU Balikpapan - Dea Adinda Larasati (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
This study was conducted during an internship at the HSSE Department of PT Kilang Pertamina Patra Niaga’s Balikpapan Refinery, which focused on electrical work due to the high risks involved such as electric shock, short circuits, and fires that can threaten worker safety and disrupt production processes. To address this, the organization uses frontline worker and supervisor checklists to implement Element 5 of the Corporate Life Saving Rules (CLSR) regarding Powered Systems. The objective of this study is to evaluate compliance with the implementation of the CLSR Element 5 checklist for electrical work at PT Kilang Pertamina Patra Niaga RU Balikpapan, as well as to identify standard operating procedures, assessment aspects, and factors that influence workers’ compliance with the checklist. The objective of this study is to evaluate compliance with the CLSR Element 5 checklist for electrical work. The research methods used were field observations, interviews, and the completion of checklists. The results showed that neither company had any unsafe categories. They also demonstrated 100 percent compliance with all relevant and assessable items. The two contractors showed differences in the scores on the frontline worker checklist and the supervisor checklist, indicating that the current stage of work affects the relevance of the assessment items. PT ABB Sakti Industri had an “N/A” percentage of 21.43% on the frontline worker checklist and 11.11% on the supervisor checklist, while PT Wifgasindo Ciel 01 had an “N/A” percentage of 57.14% on the frontline worker checklist and 27.78% on the supervisor checklist. Due to these differences, the challenges identified include incomplete documentation resulting from security officer turnover without a proper handover, as well as procedural discrepancies that cause contract officers to experience confusion when filling out the checklists due to an inadequate transfer of information.